Development of the Institute of Criminal Procedural Evidence - A. V. Smolin (Сибирское юридическое обозрение, 2024)
The fulfillment of the key function of criminal proceedings – the resolution of the case on the merits – is impossible without criminal procedural knowledge of all the circumstances of the crime committed. The foundation of this activity is criminal procedure and evidence, which is a very complex, multi-level system. The foundation of such a system is evidence. At present, there are serious contradictions in how the sources of evidentiary information, evidence of practice, and proof are interrelated. Collection, verification, evaluation and presentation of evidence, both in theory and in practice, often give rise to non-legal, unfair and unjustified criminal procedural decisions in pre-trial proceedings and in court. Despite the plethora if views on the theory of evidence, the lack of consistency in investigative and judicial practice with regard to the evidence suggests that at present there are a large number of unresolved problems in this field as well as on the legislative level. In this regard, it seems necessary to conduct a study on the historical and legal aspects of the institute of evidence and proof in domestic legislation in order to identify the prerequisites of its origin and patterns of development. The conducted research has theoretical and practical significance. First, it contributes to the development of the topic under discussion. Second, the identified regularities allow us to use them to develop recommendations on improving the current criminal procedural legislation. The author concludes that with lapse of time, the concept of evidence has changed: from a means of substantiating guilt in “evidence-argument” terms to an element of the system of evidence including source, content and procedural form. In addition, the criteria for analyzing the development of evidence law have been formulated.